Population trend and distribution of the Vulnerable common hippopotamus Hippopotamus amphibius in the Mara Region of Kenya - Kanga, E.M.; Ogutu, Joseph O.; Olff, H.; Santema, P. (Cambridge University Press, 2011)
The common hippopotamus Hippopotamus amphibius can significantly influence the dynamics of ecosystems and engender serious conflicts with people but, in Kenya, one of the species strongholds, it has been little studied or monitored. We surveyed the hippopotamus population in the Masai Mara National Reserve and the adjoining pastoral ranches in 2006 using foot counts along 155.3 km of the main rivers. We counted 4,170 hippopotamuses in 171 schools. Comparisons with earlier surveys suggest that this population increased by 169.6% between 1971 and 1980 within the reserve and, although it did not increase within the reserve during 1980–2006, it increased by 359.4% outside the reserve during this period against a background of deteriorating habitat conditions. The overall density in 2006 was 26.9 hippopotamuses km-1 of river, equivalent to a biomass of 26,677 kg km-1 of river. The ratio of calves to 100 adults was 9:100 inside the reserve, 10:100 outside the reserve and 6:100 along tributaries of the Mara River, implying that the population is either increasing or that its spatial distribution is being compressed because of range contraction. The apparent increase in the hippopotamus population contrasts with marked contemporaneous declines in the populations of most other large mammalian herbivore species in the Reserve. We discuss possible reasons underlying the increase in the hippopotamus population.